Risk of reading difficulty among students with a history of speech or language impairment: Implications for Student Support Teams - Zipoli, Richard P.; Merritt, Donna D. (Preventing School Failure: Alternative Education for Children and Youth, 2017)
Many students with a history of speech or language impairment have an elevated risk of reading difficulty. Specific subgroups of these students remain at risk of reading problems even after clinical manifestations of a speech or language disorder have diminished. These students may require reading intervention within a general education system of supports and services. The first part of this article describes three speech-language disorders that place elementary students at risk of reading problems: functional speech disorders, childhood apraxia of speech, and specific language impairment. Emphasis is given to research findings on the reading outcomes of students with these disorders. The second part of the article provides recommendations within an RTI framework that will assist Student Support Teams in identifying, monitoring, and supporting these students. © 2017 Taylor & Francis Group, LLC.
Keywords: Assessment; Language impairment; RTI; Reading disability; Speech sound disorders; dept.cmd; peer-reviewed

Interventions for Oral Language Comprehension - Zipoli, Richard P Jr; Merritt, Donna D. (Structured Literacy Interventions Teaching Students with Reading Difficulties, Grades K-6, 2022)
Keywords: dept.cmd